Penyuluhan Optimalisasi Pendapatan Ekonomi Rumah Tangga dengan Memanfaatkan Media Online di Masa Pandemi - Asti Gumartifa; Nadia Afrilliana; Lesi Agusria; Dita Adawiyah; Anggreany Hustia (Jurnal Gema Ngabdi, 2020)
In the Pandemic of Covid -19, Indonesia had a lot of changes that have occurred in society and other circles. Types of changes that occur for example; the process of teaching, learning activities and office in offline or in other words work from home. The economic income also has decreased as well as the household economic income of residents in each region. The existence of Internet facilities can greatly assist all groups of society in facing the transition of change in carrying out every work activity, and schools that usually done at home. By utilizing the Internet and computers as technology in the use of social media which is facilitated by the internet therefore the public can continue to carry out economic activities online. As the existence of social media, the community still be able to carry out in buying and selling activities to get profit and improve the household economy. The example of social media that also can be used are; instagram, facebook, whats up, and e-mail. Thus, from the use of social media, it still can help family economy income to be existed during the Pandemic of Covid -19.